Clinical simulation scenarios for the planning and management of infusion therapy by nurses - Mariana de Jesus Meszaros; Angélica Olivetto de Almeida; Ruana Luiz Ferreira da Silva; Aline Helena Appoloni Eduardo; Maria Helena de Melo Lima; Ana Railka de Souza Oliveira-Kumakura (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to build, evaluate and test two clinical simulation scenarios for the planning and management of infusion therapy by nurses. Methods: methodological study, with construction of scenarios based on the NLN Jeffries Simulation Theory and the theoretical model Vessel Health Preservation; evaluation of the scenario design by judges, with calculation of the Modified Kappa Coefficient (MKC); testing scenarios with the target audience. Results: scenarios built for: 1. Patient assessment and vascular device selection; and 2. Identification and management of deep vein thrombosis. In the evaluation by judges, testing of validated scenarios in relation to educational practices and simulation design, the items evaluated presented MKC values ≥ 0.74. Conclusion: two evidence-based scenarios related to infusion therapy were constructed, with high levels of agreement among judges regarding their design. In testing with nurses, good results were obtained regarding the design and structuring of educational practice.